Pollution mercurielle et risques sanitaires : Etat des lieux bassin-sud du Bénin - AZON, NADIA B.N.; ADOUNKPE, GNONLONFOUN JULIEN (My University, 2019)
Mercury is a metal whose physical, chemical and toxicological characteristics make it one of the most monitored metals in the world today. The Republic of Benin is certainly not industrialized; however, it presents risks of contamination of its ecosystems by mercury. This publication, as a prelude to research work on the mercury pollution of rivers in the Republic of Benin, takes stock of existing work relating to the said pollution of the waters of the southern Benin basin. It highlights some scientific work on mercury pollution in surface water, as well as plausible sources of contamination. It is apparent from publications that have addressed the issue that mercury pollution of soils and waters, with their sources, has reached disturbing limits. In fact, the use of pesticides in the cotton basin of Benin has caused mercurial pollution of the soil from 22.3 to 33 ppb. As for surface water, a mercury pollution of the order of 181.2 to 616.9 1μg / L, was obtained against 6μg / L recommended by WHO.
Keywords: mercury; mercury pollution; toxicity; aquatics ecosystems